Combination of Biological Fertilizers and Inorganic Fertilizers to Increase Productivity of Red Curly Chili (Capsicum annuum L) - Bayu Adirianto; Endang Krisnawati; Dwiwanti Sulistyowati; Aditya Dyah Utami (Tropical Plantation Journal, 2022)
Due to declining soil fertility as a consequence of continued land usage, the production of red curly chilies has decreased. Fertilization, both biological and inorganic, is one strategy that may be used. The goal of this research was to ascertain the effect of a fertilizer mixture on the growth and production of red curly chili. Land preparation, planting, application of biological and inorganic fertilizers, and observation of growth and production were all included in the study phases. The study was done in a factorial experiment with three replications, with factor 1 being biological fertilizer and factor 2 being the kind of micro fertilizer. At 0, 30, 60, and 90 days after planting, bio-fertilizers, NPK, and micro-fertilizers were applied four times. The height of the plant, the diameter of the crown, the number of chilies, the length of the fruit, the weight of the chilies, and the diameter of the chilies were all recorded. The collected data were examined statistically using Analysis of Variance (ANOVA) and the Duncan Multiple Range Test (DMRT) at the 5% and 10% levels. The findings indicated that micronutrient brand B treatment had an effect on plant growth. Plant production is affected by the use of biological fertilizers.